KARAKTERISTIK ROTI TAWAR DENGAN SUBSTITUSI TEPUNG SORGUM (Sorghum bicolor (L) MOENCH) TERFERMENTASI DAN TANPA FERMENTASI - Sari, Ardhea Mustika; Kurniawati, LInda; Mustofa, Akhmad (Jurnal Teknologi Hasil Pertanian, 2015)
This research was aimed to determine the appropriate concentration of fermented and unfermented sorghum flour for bread making which received by the panelists. Sorghum flour was naturally fermented and then dried with cabinet dryer at 60 °C for 8 h. Substitution of sorghum flour either fermented and unfermented performed at various concentration i.e 10%, 20%, 30% and 40%. Organoleptic test results showed that white bread accepted by panelists was subtituted with fermented and unfermented sorghum flour in concentration of 10% and 20%. White bread with fermented sorghum flour substitution of 10% and 20% have moisture content of28.702% and 34.392%, while white bread with unfermented sorghum flour has moisture content 28.660% and 31.857%. Ash content of white bread with fermented sorghum flour 10% and 20% were 0.823% and 0.638%, while white bread with unfermented sorghum flour 10% and 20% have ash content of 0.830% and 0.718%.Fiber content of white bread subtituted with 10% and 20% fermented sorghum flour was 3.375% and 4,206% respectively whereas white bread with 10% and 20% unfermented sorghum flour have fiber content 3.008% and 3.873%. Key words: fermentation, sorghum flour, white bread